The 'real' explanation of the PPP puzzle. Issue 5 (12th March 2017) - Ford, Nicholas; Horioka, Charles Yuji
ABSTRACT: This article shows that global financial markets cannot, by themselves, achieve net transfers of financial capital and real interest rate equalization across countries and that the integration of both global financial markets and global goods markets is needed to achieve net transfers of capital and real interest rate equalization across countries. Thus, frictions (barriers to mobility) in one or both of these markets can impede the net transfer of capital between countries, produce the Feldstein and Horioka (1980) finding of high-saving-investment correlations and prevent real interest rates from being equalized across countries. Moreover, frictions in global goods markets can explain why real exchange rates deviate from purchasing power parity (PPP) for extended periods of time and can therefore also explain the PPP puzzle. Consequently, we are able to resolve two of Obstfeld and Rogoff's (2000) '6 major puzzles in macroeconomics' with essentially the same explanation.